Modelling of Chain Process of Debris Flow Blocking River and Induced Flood Disaster in Meizoseismal Area ——A Case of Xiazhuang Gully in Wenchuan County - LUO Yuting; WANG Lijuan; MA Song; TANG Yao (Renmin Zhujiang, 2023)
After the Wenchuan earthquake,there has been a sharp increase in the frequency of debris flow activity,which is featured by low rainfall threshold,frequent occurrence,wide impact and strong destruction.The hazards mainly include siltation,impact,river blocking and inundation.Among them,the mudslide blocking river shows particularly prominent disaster effect,seriously threatening the improvement of mountain infrastructure,and residents' life and property safety.The research of the dynamic process of river blocking disaster chain of debris flow can provide scientific reference for debris flow hazard prevention and early warning.Based on field surveys,physical tests,remote sensing images and rainfall data for a typical watershed,a numerical simulation was conducted to study the dynamic process of the river blocking disaster chain of debris flow in Xiazhuang Gully.The simulation results show that the debris flow reaches the outlet of the basin at t=120 step;and at t=130 step the debris flow pushes forward and blocks part of the main river;at t=140 and 150 step the debris flow completely blocks the main river,forming a debris-dam with a length,width and thickness of 236.0 m,74.0 m,6.2 m and 312.0 m,79.0 m,and 7.1 m,respectively,which causes the upstream water level to rise,with an inundation depth of the upstream residential area of 3-5 m.By comparing the simulation results with the field measured data,the accuracy of the simulation reaches up to 84.9%,which indicates that the model is of good applicability to simulating the disaster chain process of landslide-debris flow-flood.